A Diagnostic Challenge in the Differential Diagnosis of Recurrent Seizures During Pregnancy: Epilepsy Versus Eclampsia - Andri Subiantoro; Sugiharto, Wahyu; Khaidar, Reyfal (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Seizures during pregnancy are associated with adverse outcomes for mothers and infants. Seizures during pregnancy can be associated with multiple factors. To establish effective treatment and management of seizures, it is important to identify all of the factors that may contribute to seizures during pregnancy. Objective: This study aimed to evaluate and identify the cause of seizures in pregnancy to facilitate appropriate treatment. Case Report: We present a case of a 32-week pregnant woman who experienced eclampsia and recurrent seizures during the peripartum period. The patient had a history of inadequately managed epilepsy. Seizure management required multiple medications, including magnesium sulfate, benzodiazepine, and phenytoin. The patient underwent an emergency caesarean utilizing the Rapid Sequence Intubation (RSI) procedure and general anesthesia to rescue the baby. Nicardipine, furosemide, isosorbide dinitrate, captopril, spironolactone, and hydrochlorothiazide were used to manage blood pressure. The patient needs to be continuously observed, and the therapy should be adjusted according to the patient’s condition. Discussion: The patient had a history of epilepsy and had experienced two bouts of generalized seizures with characteristics of eclampsia before being arrived at the emergency room. Determining how to control the seizures in this spesific individual was a challenge. The primary therapy of patients with active seizures should include maintaining the airway, respiration, and circulation. The therapeutic objectives are immediate delivery of a viable fetus and maintenance of maternal health. Perioperative management aims to control blood pressure and seizures, maintain hemodynamics, manage anesthesia for terminating a pregnancy, and support critical care management for any potentially fatal complications from this condition. Conclusion: Seizures in pregnancy are attributable not just to eclampsia but can also cause by another or concurrently together with other causes. Early diagnosis and appropriate treatment are required to achieve the best outcome for this patient.